Analysis Of Public Service Cauldron On Customer Satisfaction At Bank Republik Indonesia Kefamenanu Branch - Berno Benigno Mitang; Emilia Khristina Kiha (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The quality of service provides an encouragement to customers, to establish a strong bond with the company.  Such a bond in the long term allows the company to carefully understand the expectations of customers and their needs so that the company can increase customer satisfaction where the company maximizes a pleasant customer experience and minimizes the customer experience that is less pleasant. The title of the research on service quality analysis of nasbah satisfaction at Bank Rakyat Indonesia Kefamenanu Branch, while the purpose of this research is to find out how to analyze the quality of service (tangibles, reliability, resposiveness, assurance and fourty) to customer satisfaction of PT. Bank Republik Indonesia Kefamenanu Branch and in this study used Multiple Regression Analysis. The results of the validity instrument test show rhitung > rrititis means valid and reliabity is above 0.6 means reliable. The results showed multiple regression analysis, namely, Y = a + β1X1 + β2X2 + β3X3 + β4X4 + β5X5 = 8,209 + (-0.065X1) + 0.252X2 + 0.213X3 + 0.199X4 + 0.287X5. The results of the test showed the quality of service partially positively affect customer satisfaction. F test results showed that the quality of service simultaneously positively affected the customer satisfaction of the bank, where the value of Pvalue 0.000 < 0.05. The coefficient of determination (R2) shows the amount of contribution of 0.643 or 64.3% of the quality of service to customer satisfaction, while the remaining 52.8% is in the form of contributions from other factors not studied in this study.